Open source software adoption and innovation performance of SME's in South Africa . - Greyling, Barend Christiaan. (My University, 2014)
ABSTRACT Open source software (OSS) has become pervasive in the software development arena over the recent years and is used by many SMEs in South Africa in the production of products and services. Theory suggests that relative advantage can be achieved in terms of innovation performance by utilizing inbound open innovation, such as OSS, to augment limited resources available to SMEs that produce software related products and services. The purpose of this research was to investigate the nature and relative influence of OSS adoption factors on the innovation performance in the specified SME population using the technology, organization and environment (TOE) model as a theoretical framework. A self-administered online survey questionnaire was used to collect data for a quantitative analysis of the influence of OSS adoption on innovation performance in South African SMEs in the software products and services market. The key finding of this study indicates that the innovation performance of SMEs in South Africa is influenced by the adoption of open source software. There is a positive influence from the use of business and collaboration tools. The replacement of commercial business applications with their open source equivalents and the adoption of open source desktop platforms (e.g. Ubuntu) are supported by the findings. Managers of SMEs should consider migration to open source equivalent software in these categories in order to take advantage of not only the obvious direct cost saving but also the possible increase in innovation performance from OSS adoption. A surprising result is the relatively strong negative influence of perceptions around the stability and performance of open source operating systems compared their commercial counterparts. The results indicate that a negative perception of the relative stability and performance of the Linux operating system compared to the Microsoft Windows operating system leads to better innovation performance. This research has opened up a number of new avenues of investigation in the areas of innovation, open innovation, software open source software and product development in the South African SME context and contributes to this relatively new field of research by providing confirmation of the TOE model as a suitable framework for open source and innovation research via empirical study.
MBA 2014
Keywords: Open source software,Small business .